Modelo Prolab: Laborella, propuesta de solución para trabajadoras del hogar y padres de familia, brindando apoyo doméstico confiable y contribuyendo al crecimiento y formación de mujeres. - Castillo Aguilar, Marycruz Aracely (2025)
The domestic services sector in Peru faces significant challenges, especially in terms of security, trust and labor formalization. With increasing demand from families seeking support at home and the need to ensure decent conditions for domestic workers, it is crucial to promote innovative solutions that effectively address these issues. In this context, Laborella emerges, a solution designed to connect families with domestic workers safely and efficiently. This proposal not only facilitates the hiring of domestic staff, but also empowers domestic workers by offering them decent employment and professional training opportunities. Likewise, it has a rigorous verification process, which includes a review of criminal records and psychological evaluations, ensuring that families can fully trust the selected workers. To develop this solution, a methodology based on market analysis and validation with users was used, which allowed the proposal to be adapted to the specific needs of both families and domestic workers. This validation ensured that Laborella is a desired and viable solution. The viability of the business plan was validated where an economic NPV of S/. 3,934,039.23, with an Internal Rate of Return (IRR) of 141.34%, generating a social NPV of S/. 13,750,728.59, demonstrating that the proposal is not only viable for shareholders, but also has a positive impact on society, making the business a sustainable proposition. Laborella is expected to not only consolidate itself as the leading solution in the contracting of domestic services in Peru, but also serve as a reference model for the formalization and improvement of working conditions in vulnerable sectors, thus contributing to a systemic change in Peruvian society.